2014
DOI: 10.1183/09031936.00148613
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific interstitial pneumonia: survival is influenced by the underlying cause

Abstract: Idiopathic, nonspecific interstitial pneumonia (NSIP) is most often associated with various clinical disorders, including connective tissue diseases (CTDs) and chronic hypersensitivity pneumonitis (cHP). Emerging evidence also suggests that "idiopathic" NSIP may be the lung manifestation of undifferentiated CTD (UCTD). However, whether or not NSIP outcome is influenced by the underlying cause remains uncertain.This retrospective study included 127 biopsy-proven NSIP patients (65 women, mean±SD age 55±12 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 34 publications
4
50
0
1
Order By: Relevance
“…Idiopathic (non‐IPAF) f‐NSIP was a negative prognostic factor for all‐cause mortality, and survival was poorer than that for IPAF f‐NSIP and CTD‐ILD. This result was similar to a previous UCTD cohort . However, another study recently reported that survival for IPAF was worse than that for CTD‐ILD, but the results were inconsistent because multiple radiological and pathological patterns such as UIP pattern were included.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Idiopathic (non‐IPAF) f‐NSIP was a negative prognostic factor for all‐cause mortality, and survival was poorer than that for IPAF f‐NSIP and CTD‐ILD. This result was similar to a previous UCTD cohort . However, another study recently reported that survival for IPAF was worse than that for CTD‐ILD, but the results were inconsistent because multiple radiological and pathological patterns such as UIP pattern were included.…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, NSIP is heterogeneous, and outcomes of NSIP are influenced by its cause including connective tissue disease (CTD), hypersensitivity pneumonitis and undifferentiated CTD (UCTD) . Classification as UCTD with a clinical flavour of CTD associated with NSIP is a useful concept to identify the subgroup of idiopathic NSIP patients with good prognosis . New terminology of ‘interstitial pneumonia with autoimmune features (IPAF)’ was recently proposed .…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 32 also noted that the greater the amount of fibrosis in their fibrotic NSIP cases, the worse the prognosis. Nunes et al 51 reported a median survival of 50 months for patients with CHP and an NSIP picture, a survival which was, interestingly, considerably worse than that for idiopathic NSIP or NSIP associated with a connective tissue disease.…”
Section: Relationship Of Pathologic Findings In Chp Tomentioning
confidence: 99%
“…Our study population contains only iNSIP patients with no indication of connective tissue or immune disease [195]. Although the clinical features are the same, NSIP is reported to have a better prognosis than iNSIP, [196]. The incidence of iNSIP is estimated to be 3 per million [197].…”
Section: Idiopathic Nonspecific Interstitial Pneumoniamentioning
confidence: 99%